Biology and Management of Goosegrass (Eleusine indica (L.) Gaertn.) in Ornamental Plant Production - Shawn T. Steed; Christopher Marble; Nathan S. Boyd; Andrew W. MacRae; Kiran Fnu (EDIS)
This six-page fact sheet provides information about the biology and management of goosegrass, including preemergence and postemergence control options. Written by Shawn Steed, Christopher Marble, Nathan S. Boyd, Andrew MacRae, and Kiran Fnu and published by the Environmental Horticulture Department.http://edis.ifas.ufl.edu/ep538